50 years of diplomatic relations between Peru and China - Novak, Fabián (2022)
At the 50th anniversary of our diplomatic relations with the People’s Republic of China, we believe it is pertinent to reflect on the evolution of the factors that contributed, over time, to  its strengthening and consolidation, as well as its various edges and mechanisms they  present today. In this sense, this article analyzes the different stages through which this  relationship has passed, and how a comprehensive strategic partnership was progressively  built between the two countries.